A Personal Scientific Journey in Ophthalmology: Twenty-Five Years of Translating Research into Novel Therapies - Dario Rusciano (Pharmaceuticals)
Ocular diseases including glaucoma, diabetic retinopathy and age-related macular degeneration represent a growing global health burden, with current treatments often providing only symptomatic relief. Through an integrated approach combining preclinical models, molecular biology, and clinical insights, this review synthesizes 25 years of my translational research to advance therapeutic strategies for these conditions. Key findings demonstrate the following: (1) the dual neuroprotective and intraocular pressure-lowering effects of natural compounds (EGCG, forskolin) in glaucoma models; (2) successful development of Uparant, a first-in-class peptide inhibitor of pathological angiogenesis with efficacy in retinal disease models; and (3) innovative drug delivery systems (melatonin nanomicelles, liposomal sprays) that enhance ocular bioavailability. Notably, some of these approaches have progressed to early-phase clinical trials, demonstrating translational potential. Significant challenges remain in optimizing sustained drug delivery and addressing the heterogeneity of ocular diseases through personalized approaches. Future directions include combinatorial therapies and the application of artificial intelligence for treatment optimization. Collectively, this work establishes a framework for developing multi-target therapies that address both the molecular mechanisms and clinical needs in ophthalmology.